Anomalous origin of the left coronary artery from the pulmonary trunk: elucidation with colour Doppler flow mapping. Issue 1 (January 1990) - Houston, A B; Pollock, J C; Doig, W B; Gnanapragasam, J; Jamieson, M P; Lilley, S; Murtagh, E P
Abstract : Four infants and children with anomalous connection of the left coronary artery to the pulmonary trunk were studied with colour Doppler flow mapping. In three the diagnosis was only suspected when the colour Doppler study showed dilated intraseptal and epicardial vessels and an abnormal flow signal into the pulmonary artery in diastole; this latter signal localised the exact site of communication, which was not apparent on angiocardiography. Two of these patients had previously had operations for severe mitral regurgitation, the diagnosis of anomalous left coronary artery having been previously considered in one but missed despite aortic root angiography. The colour study in the fourth was largely confirmatory, operation without catheterisation being undertaken on the basis of the echocardiographic images. By contrast in two infants subsequently seen with congestive cardiomyopathy the demonstration of flow direction in the left coronary artery confirmed that it was normally connected to the aorta. Colour Doppler flow mapping can show flow direction in the left coronary artery and from the mouth of an anomalous coronary artery into the pulmonary artery, thus simplifying the diagnosis and allowing the site of the connection of the left coronary artery to the pulmonary artery to be determined with precision.